Evaluation of popularity of Integrated Modular Teaching Among Medical Students (Journal of Fatima Jinnah Medical University, 2018)
Background: Integrated Modular Teaching is a recent progress in the field of teaching, proving beneficial for both students and teachers. It is ready to take place of the traditional lecture method in medical colleges all across the world including Pakistan. Modular Teaching makes use of modules to emphasize individual learning among its users. The use of module helps medical students grasp concepts underlying any specific topic of medicine with great apprehension. Aims & Objectives: This is an attempt of researchers to analyse whether modular teaching will be advantageous for medical students in Pakistan. The research will signify how medical students respond to modular teaching in comparison to traditional teaching. The research will also help us learn how students feel about different tactics of modular teaching. Subjects & Methodology: A questionnaire was circulated among medical students all over Pakistan. The questionnaire emphasized on how modular teaching is better than traditional teaching and between the two which one do students feel more comfortable with. Later responses of 169 students were analysed. Results & Conclusions: The responses, when analysed, showed that 71% of the students chose modular teaching over traditional teaching. In order to improve the quality of teaching in medical colleges of Pakistan we need to adapt to modular teaching.